Enzymatic and Chemical Syntheses of Vacor Analogs of Nicotinamide Riboside, NMN and NAD - Lars Jansen Sverkeli; Faisal Hayat; Marie E. Migaud; Mathias Ziegler (Biomolecules, 2021)
It has recently been demonstrated that the rat poison vacor interferes with mammalian NAD metabolism, because it acts as a nicotinamide analog and is converted by enzymes of the NAD salvage pathway. Thereby, vacor is transformed into the NAD analog vacor adenine dinucleotide (VAD), a molecule that causes cell toxicity. Therefore, vacor may potentially be exploited to kill cancer cells. In this study, we have developed efficient enzymatic and chemical procedures to produce vacor analogs of NAD and nicotinamide riboside (NR). VAD was readily generated by a base-exchange reaction, replacing the nicotinamide moiety of NAD by vacor, catalyzed by Aplysia californica ADP ribosyl cyclase. Additionally, we present the chemical synthesis of the nucleoside version of vacor, vacor riboside (VR). Similar to the physiological NAD precursor, NR, VR was converted to the corresponding mononucleotide (VMN) by nicotinamide riboside kinases (NRKs). This conversion is quantitative and very efficient. Consequently, phosphorylation of VR by NRKs represents a valuable alternative to produce the vacor analog of NMN, compared to its generation from vacor by nicotinamide phosphoribosyltransferase (NamPT).